Integrated serum proteomic and N‐glycoproteomic characterization of dengue patients - Hu, Xiao; Song, Jiamin; Ye, Guoguo; Zhu, Miao; Lan, Jianfeng; Zeng, Lijiao; Ke, Zhiyi; Yuan, Jing (Journal of medical virology, 2024)
Dengue fever is a mosquito‐borne viral disease caused by the dengue virus (DENV). It poses a public health threat globally and, while most people with dengue have mild symptoms or are asymptomatic, approximately 5% of affected individuals develop severe disease and need hospital care. However, knowledge of the molecular mechanisms underlying dengue infection and the interaction between the virus and its host remains limited. In the present study, we performed a quantitative proteomic and N‐glycoproteomic analysis of serum from 19 patients with dengue and 11 healthy people. The results revealed distinct proteomic and N‐glycoproteomic landscapes between the two groups. Notably, we report for the first time the changes in the serum N glycosylation pattern following dengue infection and provide abundant information on glycoproteins, glycosylation sites, and intact N‐glycopeptides using recently developed site‐specific glycoproteomic approaches. Furthermore, a series of key functional pathways in proteomic and N‐glycoproteomic were identified. Collectively, our findings significantly improve understanding of host and DENV interactions and the general pathogenesis and pathology of DENV, laying a foundation for functional studies of glycosylation and glycan structures in dengue infection.